Interconnectedness, Systemic Crises and Recessions - Espinosa-Vega, Marco (IMF Working Papers; Working Paper ;, 2015)
This relatively simple model attempts to capture and integrate four widely held views about financial crises. [1] Interconnectedness among financial institutions (banks) can play a major role in precipitating systemic financial crises. [2] Lack of information about the quality of bank portfolios also plays a role in precipitating systemic crises. [3] Financial crises, particularly systemic ones, are often followed by severe, lengthy recessions. [4] Loss of confidence in the financial system is partly responsible for the length and severity of these recessions. In the model, banks make decisions about initiating and liquidating risky loans. Interconnectedness among their asset portfolios can obscure information about these portfolios, causing them to make inefficient decisions about liquidation, and about retention of the managers who assess credit risk. These decisions can increase the depth of recessions, and they can produce systemic financial crises. They can also reduce the effectiveness of future bank risk assessment, increasing the probability of lengthy, severe recessions. The government, acting in the interest of current and future depositors, may wish to increase the transparency of bank portfolios by limiting interconnectedness. The optimal degree of regulation, which may depend on depositors' degree of risk aversion, may not eliminate financial crises.